2013
DOI: 10.1371/journal.pone.0057280
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis of Retinal Ganglion Cells Is Not Essential to Visual Functional Recovery after Optic Nerve Injury in Adult Zebrafish

Abstract: Zebrafish central nervous system (CNS) possesses a strong neural regeneration ability to restore visual function completely after optic nerve injury (ONI). However, whether neurogenesis of retinal ganglion cell (RGC) contributes to functional recovery remains controversial. Our quantitative analysis of RGCs in different ONI models showed that almost all RGCs survived in optic nerve crush (ONC) model; while over 90% of RGCs survived in the first 2 weeks with 75% remaining after 7 weeks in optic nerve transectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
80
0
20

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(117 citation statements)
references
References 55 publications
(3 reference statements)
14
80
0
20
Order By: Relevance
“…[17][18][19][20][21][22][23][24][25][26][27] The lens in zebrafish eyes is spheroid and not ellipsoid as compared with the human eye, and as a consequence, the zebrafish eye has a much lower volume of vitreous compared with the human eye ( Figure 1a). …”
Section: Eye Structurementioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22][23][24][25][26][27] The lens in zebrafish eyes is spheroid and not ellipsoid as compared with the human eye, and as a consequence, the zebrafish eye has a much lower volume of vitreous compared with the human eye ( Figure 1a). …”
Section: Eye Structurementioning
confidence: 99%
“…28 In contrast to human ganglion cells where the retinal part of the axon is unmyelinated and the axon in the optic nerve is myelinated, in zebrafish the whole axon is myelinated to different extents. 26,27 The photoreceptor outer segment (POS) of zebrafish consists of rods and cones, comparable to the human retina. Anatomically cones are arranged in a mosaic pattern that can be categorized into four types: short single cones (SSCs)-ultraviolet (UV)-sensitive cones, long single cones (LSCs)-blue-sensitive cones, and double cones (DCs) consisting of short (green sensitive) and long (red sensitive) cones.…”
Section: Eye Structurementioning
confidence: 99%
“…In contrast, in the ONC model, the nerve is crushed with forceps to separate the axons, but leaving the connective tissue around them intact, and thus holding the proximal and distal ends together (Becker et al 2000;McCurley and Callard 2010;Fleisch et al 2011;Lemmens et al 2015;Van Houcke et al 2017). As expected, the ONT model is somewhat more drastic and regeneration progresses slower as compared to ONC (Zou et al 2013).…”
Section: Models and Methods To Study Spontaneous Optic Nerve Regeneramentioning
confidence: 96%
“…Interestingly, almost all RGCs will survive the lesion (Kato et al 2013;Zou et al 2013), which is highly contrasting to the extensive cell death observed in rodent models (Berkelaar et al 1994;Kalesnykas et al 2012;Nadal-Nicolas et al 2015b;Yukita et al 2015). The subsequent regenerative process can be divided in different major phases, based on a combination of morphological, physiological, biochemical and behavioral methods (McCurley and Callard 2010; Kato et al 2013).…”
Section: Models and Methods To Study Spontaneous Optic Nerve Regeneramentioning
confidence: 99%
See 1 more Smart Citation